2014
DOI: 10.1074/jbc.c114.602698
|View full text |Cite
|
Sign up to set email alerts
|

Human NAT10 Is an ATP-dependent RNA Acetyltransferase Responsible for N4-Acetylcytidine Formation in 18 S Ribosomal RNA (rRNA)

Abstract: Background: Post-transcriptional modifications of rRNAs play important roles in biogenesis and function of ribosome. Results: NAT10 is an ATP-dependent RNA acetyltransferase responsible for N 4 -acetylcytidine formation of 18 S rRNA. Conclusion: NAT10 and ac 4 C1842 are required for pre-18 S rRNA processing. Significance: 40 S subunit formation is regulated by a single acetylation of 18 S rRNA, implying a regulatory mechanism for ribosome biogenesis by sensing the cellular energy budget.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
210
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(225 citation statements)
references
References 24 publications
6
210
0
Order By: Relevance
“…NGDN has been originally implicated in translational control in neuronal cells (47), but belongs to the ‘U three protein’ (UTP) 3 protein family of SSU processome components by sequence similarity. In addition to NOL10 and NGDN, other nucleolar factors were detected in the MS analysis, including the predicted SSU processome component NAT10 (21), an RNA cytidine acetyltransferase already linked to 40S ribosomal subunit biogenesis (31,48,49). …”
Section: Resultsmentioning
confidence: 99%
“…NGDN has been originally implicated in translational control in neuronal cells (47), but belongs to the ‘U three protein’ (UTP) 3 protein family of SSU processome components by sequence similarity. In addition to NOL10 and NGDN, other nucleolar factors were detected in the MS analysis, including the predicted SSU processome component NAT10 (21), an RNA cytidine acetyltransferase already linked to 40S ribosomal subunit biogenesis (31,48,49). …”
Section: Resultsmentioning
confidence: 99%
“…(40) NAT10 knockdown decreases proliferation in several cancer cell types. (36,41) Our data demonstrates a direct role for Nat10 overexpression in liver tumorigenesis in a mouse model regardless of steatosis. One study found no significant correlation between high NAT10 expression and patient gender, age, or hepatic cirrhosis.…”
Section: Discussionmentioning
confidence: 54%
“…NAT10 is a lysine and RNA acetyltransferase with a variety of reported acetylation targets and functions, including regulating gene expression, cell division, and precursor rRNA processing. (3436) Normal expression is required for the formation of N4-Acetylcytidine-modified rRNA, essential for 18S rRNA formation during ribosome biogenesis. (36) The rate of ribosome biogenesis regulates cell proliferation(37) and could be rate-limiting in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This triphosphate plays a central role not only in storage of metabolic energy, but also in signal transduction (Buzzi et al, 2010;Eliston et al, 1998;Jones, 1972). Intracellular ATP levels have been used as indicators for cell viability as well as many diseases such as hypoxia, hypoglycemia, ischemia, Parkinson's disease, and some malignant tumors (Dale and Frenguelli, 2009;Evans et al, 2004;Kahlin et al, 2014;Keane et al, 2011;Ito et al, 2014). In addition, in food and agricultural chemistry, and in the health sciences, measurements of ATP concentrations in real samples are required for bacteria detection in order to prevent food-borne illnesses (Jin et al, 2015).…”
Section: Introductionmentioning
confidence: 98%